Meningkatkan Kemampuan Pemahaman Dan Motivasi Belajar Siswa SMP Dalam Menyelesaikan Masalah Teorema Pythagoras Menggunakan Problem Based Learning - Neng Titasari; Heris Hendriana; Wahyu Setiawan (Journal on Education, 2019)
The background of this research is the low ability of students' mathematical understanding and learning motivation of junior high school students. This study aims to determine the ability of students' mathematical understanding and student motivation to learn using the Problem Based Learning approach. The method used in this study is an experimental method with a pretest and posttest group design. The population in this study were all eighth grade students of SMPN 1 Margaasih in Bandung Regency. The sample in this study were two classes from class VIII, namely class VIII F as Experiment I class and VIII G as Experiment II class. The research data were obtained through tests of students' mathematical understanding abilities and student mathematics learning motivation questionnaires. Based on quantitative data analysis, it can be concluded that the ability of students' mathematical understanding and learning motivation of junior high school students whose learning uses the Problem Based Learning approach increases.